Ensuring donor safety: is venesecting therapeutic donors to haemoglobin levels below Blood Service guidelines safe?. Issue 4 (20th February 2020) - Lim, Zixiang; Bentley, Peter; Olynyk, John K.
Abstract : Therapeutic phlebotomy is the cornerstone of treatment for HFE haemochromatosis (HH). Current Australian Red Cross LifeBlood Service guidelines mandate measuring haemoglobin (Hb) levels prior to phlebotomy and if below 130 g/l in men or 120 g/l in women, donors are deferred from donating whole blood. Therapeutic donation below these levels may take place where both the treating doctor and a blood service medical officer approve. The aim of the current study was to determine whether adverse events are more frequent in those who undergo therapeutic phlebotomy below current Hb thresholds applied to volunteer therapeutic donors. A retrospective review of all therapeutic donations was undertaken for the financial year 2016–2017. The data were obtained through the Australian Red Cross Blood Service. Inclusion criteria were any donor between 16 and 70 years of age, weighing more than 50 kg and meeting blood service guidelines for donation. All adverse events recorded in an electronic quality system were obtained and associated with donor haemoglobin level. Statistical analyses were performed using analysis of variance or Fisher's exact test (GraphPad Prism). About 34 886 therapeutic phlebotomy donations occurred during 2016–2017, of whom the majority were referred for HH (34 089). In total, 365 of 34 886 donations (0·0105%) were complicated by an adverse event. A total of 305 (0·0087%) therapeutic donations occurred while below the lower limit of blood service Hb threshold for their respective genders. Of the donations that occurred below the blood service threshold, 3 of 305 (0·0098%) had an adverse event compared with 362 of 34 581 donations above the lower limit threshold (0·0105%, P = 0·99). The incidence of adverse events was not increased in the group which underwent therapeutic phlebotomy below the current Australian Red Cross Blood Service Hb threshold compared with those above threshold, indicating safety of treatment at Hb levels lower than currently recommended.